The construction of a parallel discursiveness in the Spanish class for refugee population (Letras, 2019)
From 1997 to 2008 (Luppino) and 1998 to 2004 (Cerqueiras) we were in charge of Spanish classes for refugees, under the sponsorship of the ACNUR- High Commission of the United Nations for Refugees-, the FCCAM- Argentinean Catholic Migration Commission and the UBA -University of Buenos Aires-.Spanish classes were shared by two or more instructors, who decided to take notes during and after classes, which became over time in a kind of “logbooks”.This paper tries to give an account of the process of construction of this shared textuality (the logbooks) among the teachers in charge of the courses, describe the generated discourses and their topics, examine their curricular decisions and methodological interventions, analyze them  from an ethnographic perspective (Guber, 2001 and 2005; Rockwell 2009) and review them based on the concepts of field notes (Taylor and Bogdan, 1987) that is, as a technical tool that facilitates inquiry from observation and participation.The construction of a parallel discursiveness in the Spanish class for refugee population
Keywords: Spanish FL Teaching – Refugees – Journal of Notes – Logbook – Parallel Discursivity – Register